Pengaruh Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Kinerja Keuangan Perusahaan Dengan Kebijakan Deviden Sebagai Pemoderasi - Nilayanti, Mila; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p03, 2019)
This study aims to determine the effect of managerial and institutional ownership on corporate financial performance with dividend as a moderating variable. The population is all banking companies listed in 2012-2016 periods. The sample was chosen using purposive sampling method. The financial performance is measured by ROA, managerial ownership is calculated by the ratio of shares owned by the manager with the number of shares outstanding, the institutional ownership is calculated by the ratio of shares owned by the institution with the number of shares outstanding, and the dividend measured by the DPR. Data analysis techniques used are descriptive statistical test, classical assumption test, and MRA. Test results show that managerial ownership does not affect the financial performance, institutional ownership positively affects the financial performance, dividend can strengthen the influence of institutional ownership on the financial performance and unable to moderate the effect of managerial ownership on the financial performance. Keywords : F inancial performance, managerial ownership, institutional ownership, dividend policy, banking